Genetic characterization and mapping of the shell-strength trait in peanut - Gilad Ben Israel; Srinivas Kunta; William Mlelwa; Arye Harel; Kapil Gupta; Yael Levy; Shmuel Galili; Ran Hovav (BMC Plant Biology)
Abstract Background Shell strength is an important trait in peanuts that impacts shell breakage and yield. Despite its significance, the genetic basis of shell strength in peanuts remains largely unknown, and the current methods for rating this trait are qualitative and subjective. This study aimed to investigate the genetics of shell strength using a segregating recombinant-inbred-line (RIL) population derived from the hard-shelled cultivar ‘Hanoch’ and the soft-shelled cultivar ‘Harari’. Results Initially, a quantitative method was developed using a texture analyzer, focusing on the proximal part of isolated shells with a P/5 punching probe. This method revealed significant differences between Hanoch and Harari. Shell strength was then measured in 235 RILs across two distinct environments, revealing a normal distribution with some RILs exhibiting shell strength values beyond those of the parental lines, indicating transgressive segregation. Analysis of variance indicated significant effects for the RILs, with no effects of block or year, and a broad-sense heritability estimate of 0.675, indicating a substantial genetic component. Using an existing genetic map, we identified three QTLs for shell strength, with one major QTL (qSSB02) explaining 18.7% of the phenotypic variation. The allelic status of qSSB02 corresponded significantly with cultivar designation for in-shell or shelled types over four decades of Israeli peanut breeding. Physical and compositional analyses revealed that Hanoch has a higher shell density than Harari, rather than any difference in shell thickness, and is associated with increased levels of lignin, cellulose, and crude fiber. Conclusions These findings provide valuable insights into the genetic and compositional factors that influence shell strength in peanut, laying a foundation for marker-assisted selection in breeding programs focused on improving pod hardness in peanuts.